Recent Advances on Familial Hypercholesterolemia in Children and Adolescents - Francesca Mainieri; Veronica Maria Tagi; Francesco Chiarelli (Biomedicines, 2022)
Familial hypercholesterolemia is a common autosomal hereditary disorder characterized by elevated concentrations of low-density lipoprotein cholesterol and the development of premature atherosclerosis and cardiovascular disease. Early diagnosis, as well as prompt and aggressive treatment, are fundamental steps to prevent cardiovascular complications and a high rate of premature mortality in children and adolescents. Clinics and genetics are the two main aspects on which diagnosis is based. Widespread screening programs are a respectable option for the early detection of familial hypercholesterolemia. Different types of screening have been proposed so far; however, the optimal screening program has not yet been found. The treatment approach for both heterozygous and homozygous familial hypercholesterolemia in the pediatric population is multidisciplinary, including lifestyle modifications, standard lipid-lowering medications, and novel pharmacological agents. The latter show promising results, especially for patients who experience intolerance to other treatment or present with more severe conditions. Our purpose is to focus on the importance of the early detection of familial hypercholesterolemia, and to highlight the best therapeutic strategies, including the recent approaches based on current clinical evidence, that need to be adopted from the earliest stages of life.